You literally just need to click yes then call it a day it’s simple don’t worry too much :D
The formula for the hypotenuse of a triangle is:
[a squared] plus [b squared] = c squared
a and b represent the two sides of the triangle.
You would have to square 8 and 4, add them, then take the square root of it to find the length of the hypotenuse.
<h2>The first equation is correct.</h2>
Answer:
for the first equation
f(-3) = 34
f(4) = 6
for the 2nd equation
f(-3) = -56
f(4) ÷ 70
Step-by-step explanation:
my work is attached in a picture.
all you do is substitute each x value into each equation
Answer:
SAS
Step-by-step explanation:
ΔABD ~ ΔECD is similar through:
S - because ED = CD (Given)
A - same angle ∠D (Statement 2)
S - because AD = BD (Given)
Cheers!